Computer Management of Medical Records, External Consultations and Archives in a Gastro-Enterology Department - Cornee, Jacqueline; Chanon, M.; Trouve, C.; Rodriguez, M. (Methods of Information in Medicine, 1977)
This paper describes the processing of medical data of in-patients in a gastro-enterological department. The project has three aims:—Setting up medical information according to a logical procedure akin to medical thinking and projecting the data in a form similar to classical medical observation;—Establishing a data bank of which the data may be directly evaluated with statistical methods; —Setting up a patient card index which is kept up to date automatically in the case of re-admission to the hospital or consultation.The program uses a table of 2,300 items. The items correspond to subjective symptoms as well as objective findings. A close relation was established between each item and the time of its observation, in order to be able to exactly describe the entire course of the illness. As a result we obtain—a computer listing with all medical information in triplicate (one copy for the physician, one for the hospital archives and a third one for the information retrieval department);—a computer-edited archive (every week information on newly admitted and released patients as well as on all external consultations is brought up to date in three different categories, according to medical record number, in alphabetical order and according to a key for diagnoses).The procurement of information was integrated into the daily hospital routine, a voluntary participation of the medical personnel being aimed at. Thus, data processing does not demand any additional personnel.Patient data stored by the computer calls for new legislation for the protection of patients, in particular in order to protect the rights of the individuum as against automation and to warrant an accurate control of the data stored.
Keywords: Medical Record; Gastro-Enterology; Computer Processing; Data Bank